1987
DOI: 10.3171/jns.1987.66.5.0706
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging and computerized tomography in relation to the neurobehavioral sequelae of mild and moderate head injuries

Abstract: Twenty patients admitted for minor or moderate closed-head injury were studied to investigate the relationship between magnetic resonance imaging (MRI) and neurobehavioral sequelae. The MRI scans demonstrated 44 more intracranial lesions than did concurrent computerized tomography (CT) scans in 17 patients (85%); most of these lesions were located in the frontal and temporal regions. Estimates of lesion volume based on MRI were frequently greater than with CT; however, MRI disclosed no additional lesions that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
124
0
1

Year Published

1990
1990
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(133 citation statements)
references
References 23 publications
8
124
0
1
Order By: Relevance
“…Finally, the failure to find deficits in the verbal fluency skills of the mild TBI group is consistent with the findings of Leininger et al (1990) but not with those of Fos et al (1995), Levin et al (1991), and Mathias and Coats (1999). Non-verbal fluency, on the other hand, was clearly compromised in the mild TBI group; a finding supported by Levin et al (1987Levin et al ( , 1991 in the acute stages after a mild TBI (around the time of the injury) but not in the more chronic phases (i.e., 1-3 months post injury). Importantly, the effects observed here accord very well with those reported by Zakzanis et al (1999) who noted, in their meta-analysis of mild TBI research, that the domains with the greatest observed deficits are cognitive flexibility (assessed here by the RFFT, COWA), followed by delayed recall (RAVLT short and long delayed recall), memory acquisition (RAVLT Trials 1-5), attention and concentration (TEA subtests) and verbal ability (not assessed).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Finally, the failure to find deficits in the verbal fluency skills of the mild TBI group is consistent with the findings of Leininger et al (1990) but not with those of Fos et al (1995), Levin et al (1991), and Mathias and Coats (1999). Non-verbal fluency, on the other hand, was clearly compromised in the mild TBI group; a finding supported by Levin et al (1987Levin et al ( , 1991 in the acute stages after a mild TBI (around the time of the injury) but not in the more chronic phases (i.e., 1-3 months post injury). Importantly, the effects observed here accord very well with those reported by Zakzanis et al (1999) who noted, in their meta-analysis of mild TBI research, that the domains with the greatest observed deficits are cognitive flexibility (assessed here by the RFFT, COWA), followed by delayed recall (RAVLT short and long delayed recall), memory acquisition (RAVLT Trials 1-5), attention and concentration (TEA subtests) and verbal ability (not assessed).…”
Section: Discussionsupporting
confidence: 81%
“…However, objective assessments of memory have provided mixed findings. Whereas Gentilini et al (1985), Levin et al (1987), and Mathias and Coats (1999) found no evidence to indicate visual or verbal memory problems at 1 month post injury, other studies have shown significantly poorer working memory (Newcombe et al, 1994) and delayed recall (Dikmen et al, 1986) at similar post-injury intervals. Prob-lems with verbal learning (Leininger et al, 1990) and delayed recall (Stuss et al, 1985) have additionally been reported in chronically affected mild TBI patients at 3 and 5 months post injury, respectively.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17] These studies indicate that although subtle forms of neural injury can be better detected by MRI, and that isodense subdural collections (as may be found in chronic subdural injuries in adults) also may be more readily identified, in acute settings with children MRI offers no advantage in detecting lesions of clinical concern. We conclude from this literature that 1) although an abnormal skull film increases the likelihood of a significant intracranial lesion, the test is not of sufficient sensitivity or specificity to be clinically useful in most settings, and 2) CT is sufficiently sensitive and specific as the imaging modality of choice at this time; in most cases, a normal CT scan in a child who meets the case definition provides assurance that subsequent adverse outcomes are very unlikely.…”
Section: Imaging Modalitiesmentioning
confidence: 91%
“…MRI is superior to CT in detecting axonal injury, small areas of contusion, and subtle neuronal damage. 49,50 Studies have shown that CT missed approximately 10 -20% of abnormalities seen on MRI. 51,52 Moreover, MRI is better at imaging the brainstem, basal ganglia, and thalami.…”
Section: Imaging and Acute Managementmentioning
confidence: 99%